Sino nasal inhalation of isotonic versus hypertonic saline (6.0 %) in CF patients with chronic rhinosinusitis: results of a multicenter, prospective, randomized, double-blind, controlled trial - Mainz, Jochen; Schumacher, Ulrike; Schädlich, Katja; Hentschel, Julia; Koitschev, Christiane; Koitschev, Assen; Riethmüller, Joachim; Prenzel, Freerk; Sommerburg, Olaf; Wiedemann, Bärbel; Staab, Doris; Gleiber, Wolfgang; et al. (Journal of cystic fibrosis, 2016)
BACKGROUND: Chronic rhinosinusitis is a hallmark of Cystic fibrosis (CF) impairing the patients' quality of life and overall health. However, therapeutic options have not been sufficiently evaluated. Bronchial inhalation of mucolytic substances is a gold standard in CF therapy. Previously, we found that sinonasal inhalation of dornase alfa as vibrating aerosol reduces symptoms of chronic rhinosinusitis more effectively than NaCl 0.9% (net treatment benefit: -5.87±2.3 points, p=0.017; SNOT-20 total score). This multicenter study compares the effect of NaCl 6.0% vs. NaCl 0.9% following the protocol from our preceding study with dornase alfa. - METHODS: Sixty nine CF patients with chronic rhinosinusitis in eleven German CF centers were randomized to receive sinonasal vibrating inhalation of either NaCl 6.0% or NaCl 0.9% for 28days. After 28days of wash-out, patients crossed over to the alternative treatment. The primary outcome parameter was symptom score in the disease-specific quality of life Sino-Nasal Outcome Test-20 (SNOT-20). Additionally, pulmonary function was assessed, as well as rhinomanometry and inflammatory markers in nasal lavage (neutrophil elastase, interleukin (IL)-1β, IL-6, and IL-8) in a subgroup. - RESULTS: Both therapeutic arms were well tolerated and showed slight improvements in SNOT-20 total scores (NaCl 6.0%: -3.1±6.5 points, NaCl 0.9%: -5.1±8.3 points, ns). In both treatment groups, changes of inflammatory parameters in nasal lavage from day 1 to day 29 were not significant. We suppose that the irritating properties of NaCl 6.0% reduced the suitability of the SNOT-20 scores as an outcome parameter. Alternative primary outcome parameters such as MR-imaging or the quantity of sinonasal secretions mobilized with both saline concentrations were, however, not feasible. - CONCLUSION: Sinonasal inhalation with NaCl 6.0% did not lead to superior results vs. NaCl 0.9%, whereas dornase alfa had been significantly more effective than NaCl 0.9%.